1974
DOI: 10.1017/s0003356100022741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of production records from a lowland sheep flock. 4. Factors influencing the incidence of successful pregnancy in young females

Abstract: SUMMARYOver a 15-year period nearly 2000 young females were exposed to the ram at 6 to 9 months of age. These Clun Forest females were born between January and April in the Cockle Park experimental flock, and mated between October and December of the same year. On average nearly 42% of those present at lambing did not produce a lamb. Analyses are presented of the reproductive efficiency of these animals and of some of the possible causes of their failure to lamb. Observations in 10 of these years suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

1980
1980
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
0
13
1
1
Order By: Relevance
“…Keane (l974b) concluded that there was no relationship between hogget body weight and any aspect of reproduction in hoggets weighing over 40 kg at mating. Bichard et al (1974) reported a linear relationship between mating weight of ewe Iambs (in 2.3 kg ranges from 25 to 60 kg) and the proportion of hoggets lambing in each weight range. Their regression coefficient, pooled over 15 years, was + 1.1 % per kg increase in mating weight, but, between years, there was a large variation in the regression coefficients (-0.7 to +3.8).…”
Section: Hogget Live Weight and Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Keane (l974b) concluded that there was no relationship between hogget body weight and any aspect of reproduction in hoggets weighing over 40 kg at mating. Bichard et al (1974) reported a linear relationship between mating weight of ewe Iambs (in 2.3 kg ranges from 25 to 60 kg) and the proportion of hoggets lambing in each weight range. Their regression coefficient, pooled over 15 years, was + 1.1 % per kg increase in mating weight, but, between years, there was a large variation in the regression coefficients (-0.7 to +3.8).…”
Section: Hogget Live Weight and Fertilitymentioning
confidence: 99%
“…The present data do not support such a simple relationship within a flock. The relationship was considered to be sigmoid rather than linear within the range oflive weights observed by Bichard et al (1974), and an interaction existed between live weight and age of dam (Fig. 1).…”
Section: Hogget Live Weight and Fertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail address: rungerfeld@gmail.com The ram effect can also be used to stimulate the reproductive activity in female ewes in other physiological conditions, as postpartum rebreeding (Ungerfeld and Sánchez-Dávila, 2012) or associate it with oestrous synchronization treatments in cyclic ewes (Ungerfeld et al, 2005;Ungerfeld, 2011). As the introduction of rams also induces an increase of LH secretion that ends in ovulation in female lambs (Knights et al, 2002), it may be used to advance puberty in extensively managed flocks (Bichard et al, 1974). However, in general, oestrus, ovulation and conception rates are lower in ewe lambs than in adult ewes (for review see: Kenyon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…and reduced litter size (Quirke et al, 1983;Hamra and Bryant, 1979). There is evidence to suggest fertility may vary with stage of breeding season and although some investigations (Bichard, Younis, Forrest and Cumberland 1974;Edey, Kilgour and Bremner 1978;Williams, Lawson, Cumming and Howard, 1978) have failed to detect a statistically significant trend, Hare and Bryant (1985) reported embryo losses to be 20% higher in animals mated at puberty compared with second or third oestrus. Collectively, these results suggest that it should be possible to maximize fertility by mating animals at third oestrus.…”
Section: Introductionmentioning
confidence: 99%